Performance analysis and optimization of integrated waste heat recovery for MEA-based onboard carbon capture and CO2 liquefaction in marine applications - Sahin, Kaan Hakan; Karakurt, Asim Sinan (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
This study examines the effect of waste heat recovery (WHR) on the energy effectiveness of onboard carbon capture and liquefaction of carbon dioxide (CO2). The employed methodology involves monoethanolamine-based (MEA-based) chemical absorption, which is particularly applicable to exhaust gas emissions from maritime vessels. The study conducts simulations using Aspen Plus (R) to examine the effects of waste heat recovery: Case 1 uses no improvements, Case 2 uses only exhaust waste heat, and Case 3 uses both exhaust waste heat and the heat from the hot CO2 gas during liquefaction. This waste heat integration (Case 3) has led to a 51.2% reduction in the reboiler duty (from 4340 kW to 2116 kW) and a corresponding 50.9% improvement in the specific reboiler duty, dropping from 7091 MJ/(ton CO2) to 3480 MJ/(ton CO2). Subsequently, the study conducts six simulations at 75% main engine load, varying capture rates to assess their effects. Varying main engine loads were also simulated to achieve an 80% capture rate. The trade-off between the European Union Emissions Trading System (EU-ETS) carbon tax revenue and the additional fuel cost for the process was evaluated economically across different capture rates and cases. The economic evaluation found an annual profit of 890,000 EUR to be achievable with a 90% carbon capture rate. Furthermore, a comprehensive secondlaw analysis based on entropy generation was conducted to evaluate the system's irreversibilities. The parametric analysis results indicate the 80% carbon capture rate to reach the thermodynamic optimum, with a minimum specific reboiler duty of 2593 MJ/(ton CO2).
Keywords: Carbon capture; Decarbonization; Onboard carbon capture systems; Ship-based carbon capture; Waste heat recovery; CO 2 emissions; Ship emissions; MONOETHANOLAMINE AQUEOUS-SOLUTION; THERMODYNAMICS; GENERATION; CHALLENGES; KINETICS; Mechanics